2015
DOI: 10.1097/rti.0000000000000123
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Screening for Lung Cancer

Abstract: CT screening is feasible in a diverse inner-city population with the support of a robust infrastructure. Further study is needed to determine whether CT screening will confer a mortality benefit in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This is consistent with NLST findings and rates reported by Milch et al and Wilson et al (both 2%) but is slightly higher than the 1-2% lung cancer yield reported by other studies. 3,9,11,12,33 A higher proportion of lung cancers identified via screening at KPCO were diagnosed at potentially curable stages I-IIIA than reported by Lanni et al in a different LCS setting (74.6% vs. 39%). 11 There is a clinically significant trend toward lower rates of advanced cancers in the postcohort, suggesting that more stringent adherence to eligibility criteria may lead to important improvements in screening outcomes.…”
Section: Clinical Characteristics and Health Outcomesmentioning
confidence: 78%
See 3 more Smart Citations
“…This is consistent with NLST findings and rates reported by Milch et al and Wilson et al (both 2%) but is slightly higher than the 1-2% lung cancer yield reported by other studies. 3,9,11,12,33 A higher proportion of lung cancers identified via screening at KPCO were diagnosed at potentially curable stages I-IIIA than reported by Lanni et al in a different LCS setting (74.6% vs. 39%). 11 There is a clinically significant trend toward lower rates of advanced cancers in the postcohort, suggesting that more stringent adherence to eligibility criteria may lead to important improvements in screening outcomes.…”
Section: Clinical Characteristics and Health Outcomesmentioning
confidence: 78%
“…Adhering to eligibility guidelines is a common barrier in LCS; McKee et al reported that 18% of patients screened did not meet eligibility criteria, and Milch et al reported that 38% did not meet criteria. 9,12 The most common reason for ineligibility was missing, incomplete, or outdated smoking history data (i.e., smoking status, quit dates, and pack-year history). 32 However, consistent with the findings of Triplette et al, additional provider and health system resources are needed to capture complete smoking history and eligibility for every patient, 35 as was the case for KPCO.…”
Section: The Lcs Processmentioning
confidence: 99%
See 2 more Smart Citations
“…With reference to the inclusion and exclusion criteria, the literature was initially screened, and 463 papers were eliminated by reading the titles and abstracts. Then, the remaining papers were read in full, 224 papers were excluded, and 48 papers [4,12–58] were finally included. The literature screening process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%